ANALISIS KEBUTUHAN SISWA DALAM PEMBELAJARAN BAHASA INGGRIS DI PONDOK PESANTREN - Habibah, Nur (Universitas Muhammadiyah Muara Bungo, 2020)
The aim of this study was to describe what are students’ need in their effort to learn English at Al Baqiyatus Sholihat Islamic Boarding School. This research was descriptive quantitative research. The subject of this study were 180 respondents. The finding of the data showed that most of students have been learning English for 1,5 and they only learn English at Islamic boarding school and no one of students learn English outside of the school. Based on students attitude towards their English language learning, the majority of students learn English because they want to pass the exam (78.33%) and they can use internet better (75.00%). Based on students’ English language skill, the researcher found that listening (87.22%) became students’ favorite skill and reading (72.2%) became the difficult skill or the skill that students need to more practice. Refers to the way student learn that most of students like to learn English by working as a whole class (92.22%) and reading text/stories (78.33%). Students like to learn vocabularies by hearing new words (81.67%) then, students learned grammar by doing written exercise at school (75.00%) and by oral practice in class (63.89%). Refers to the English favorite topic that most of students like the topic such as family/friends/people/relationship (93.89%) and they like the topic that related with Islam knowledge.